PERAN LEMBAGA KEUANGAN MIKRO SYARIAH (LKMS) DALAM MENDUKUNG EKONOMI KERAKYATAN DAN PENGENTASAN KEMISKINAN UMAT - Ayunda, Antin; Ramadhani, Indri Gayatri; Fahlevy, Reza; Hayati, Fitri (LP2M Universitas Bina Bangsa, 2025)
Many countries, including Indonesia, still face important problems, namely poverty. As of March 2024, based on data from the Central Statistics Agency (BPS), 25.22 million people from the total population of Indonesia live below the poverty line. This study aims to explore the strategic role of Islamic Microfinance Institutions (LKMS) in two aspects, namely supporting the development of the people's economy and poverty alleviation. Islamic Microfinance Institutions (LKMS) play an important role in supporting the people's economy and poverty alleviation in Indonesia. LKMS also helps the community through the management of social funds such as zakat, ifaq, sadaqah and waqf (ZISWAF), which support productive businesses in poor communities and improve their welfare. Overall, LKMS has succeeded in increasing financial inclusion by reaching previously marginalized populations and helping to combat poverty through fair and sharia-based financing. However, to reduce the impact of sharia financial products, the problem of financial literacy and public understanding of it must be resolved